2006
DOI: 10.1021/es060009m
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and Product Identification of [14C]Hexabromocyclododecane in Wastewater Sludge and Freshwater Aquatic Sediment

Abstract: In a previous study the biodegradation of hexabromocyclododecane (HBCD) was reported to occur under realistic environmental concentrations in soils and freshwater aquatic sediments with biotransformation half-lives ranging from approximately 2 days to 2 months. In this study we extend our knowledge as to the environmental behavior of HBCD with respect to the fate of the three major diastereomers of HBCD (alpha, beta, and gamma) as well as to the identification of major intermediate metabolites formed during de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 23 publications
5
59
0
Order By: Relevance
“…Yet, our results on additional transformation products indicated that only a fraction of the HBCD in the reaction mixtures was debrominated completely by the synthetic FeS into CDT within the time frame of this study. On the one hand, two tetrabromocyclododecene (TBCDe) isomers and five DBCDi isomers were identified as less brominated BCD intermediate products (see Text A4 and Table A6 for more details on the identification) by comparing their mass spectra with those of the corresponding transformation products reported in the literature (Barontini et al, 2001;Davis et al, 2006). Moreover, most of these intermediate products were still observed at the end of the experiment (48 h, Fig.…”
Section: Transformation Products and Pathway Of Hbcdmentioning
confidence: 86%
See 3 more Smart Citations
“…Yet, our results on additional transformation products indicated that only a fraction of the HBCD in the reaction mixtures was debrominated completely by the synthetic FeS into CDT within the time frame of this study. On the one hand, two tetrabromocyclododecene (TBCDe) isomers and five DBCDi isomers were identified as less brominated BCD intermediate products (see Text A4 and Table A6 for more details on the identification) by comparing their mass spectra with those of the corresponding transformation products reported in the literature (Barontini et al, 2001;Davis et al, 2006). Moreover, most of these intermediate products were still observed at the end of the experiment (48 h, Fig.…”
Section: Transformation Products and Pathway Of Hbcdmentioning
confidence: 86%
“…During each step, two Br atoms could be removed from two vicinal carbons and a double bond was subsequently formed between the two adjacent carbon atoms. Such a pathway was believed to be also operative in the microbially mediated debromination of HBCD (Davis et al, 2006), whilst part of this pathway has been proposed recently for the reductive debromination of HBCD by nanoscale ZVI (Tso and Shih, 2014). The scenario that abiotic and biotic reductive debromination of HBCD may share some common reaction steps deserves further investigation, since it likely has important implications for the remediation of anoxic sediments contaminated by HBCD.…”
Section: Transformation Products and Pathway Of Hbcdmentioning
confidence: 97%
See 2 more Smart Citations
“…Tissue-specific accumulation of a-and g-HBCD was also reported in the study of bib and whiting 30 and juvenile rainbow trout, 32 in which a preferential accumulation of a-HBCD was found in the liver. In addition, the apparent concentrations in these tissues could also be affected by biotransformation, metabolism, biodegradation and more, which were previously discussed in the studies on cytochrome P450 mediated biotransformation in marine mammals, 33 metabolites and biodegradation of HBCD in rats 34,35 and bioisomerization of HBCD isomers in fish. 36 Compared with the distribution in other environmental matrices, the elevated ratio of a-HBCD in the aquatic species could probably be affected by factors such as physical-chemical properties (aqueous solubility and half life in the environment) of the three isomers and isomer-specific bioavailability in the organisms.…”
Section: Hbcd In Aquatic Speciesmentioning
confidence: 98%